2018
DOI: 10.1038/s41598-018-32384-4
|View full text |Cite
|
Sign up to set email alerts
|

A case of behavioural diversification in male floral function – the evolution of thigmonastic pollen presentation

Abstract: Obvious movements of plant organs have fascinated scientists for a long time. They have been studied extensively, but few behavioural studies to date have dealt with them, and hardly anything is known about their evolution. Here, we present a large experimental dataset on the stamen movement patterns found in the Loasaceae subfam. Loasoideae (Cornales). An evolutionary transition from autonomous-only to a combination of autonomous and thigmonastic stamen movement with increased complexity was experimentally de… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 95 publications
(122 reference statements)
1
11
0
Order By: Relevance
“…In some species, additional mechanisms to extend the period of pollen release have evolved, including ones that release pollen in response to pollinator visits (e.g. Erbar and Leins 1995 ; Henning et al 2018 ; Mione and Diaz 2020 ). However, pollen release can also end well before flowers close (e.g.…”
Section: Connections Between Floral Signals and Rewardsmentioning
confidence: 99%
“…In some species, additional mechanisms to extend the period of pollen release have evolved, including ones that release pollen in response to pollinator visits (e.g. Erbar and Leins 1995 ; Henning et al 2018 ; Mione and Diaz 2020 ). However, pollen release can also end well before flowers close (e.g.…”
Section: Connections Between Floral Signals and Rewardsmentioning
confidence: 99%
“…Based on this report, in order to find a balance between the frequency of pollinator visits and the duration of visits, the plants increase the availability of flowers and the heterogeneity of their nectar content. The ability of plants to ‘remember’ and ‘learn’ from previous pollinator visits has been observed in some Losaceae (Henning et al, 2018). In particular, the research group of Moritz Mittelbach and Tilo Henning observed that the Nasa poissoniana ‘learns’ the frequency of pollinator visits and presents a new stamen (thigmonastic movements) immediately before arrival of the insect.…”
Section: Flowers Nectar and Fertilizationmentioning
confidence: 99%
“…This plant has developed a high stem with the aim of speeding up growth and competing to reach sunlight (Yen, 2016). The plants belonging to the Phyllostachys genus show strong intraspecific competitive capacities that make them more sensitive to some ecological niches (Sandhu et al, 2013;Yen, 2016;Inoue et al, 2018). Furthermore, specific hormones, involved in photosynthetic function, and in organization and differentiation of the parenchyma tissue (He et al, 2002), regulate this adaptive capacity.…”
Section: Introductionmentioning
confidence: 99%
“…No pollinator observations are available for this species, but based on flower morphology, it likely falls into the group of taxa predominantly pollinated by rather specialised short-tongued bees (Weigend and Gottschling 2006; Henning et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…These have proved to be informative to infer the phylogenetic relationships in Loasoideae (Weigend et al 2004; Hufford et al 2005; Weigend and Gottschling 2006; Acuña et al 2017). Sequences were newly generated for this study or for previously published research by our working group (Acuña et al 2017, 2018; Henning et al 2018). These were combined in a single matrix with 4 partitions.…”
Section: Methodsmentioning
confidence: 99%